miR-21 in Human Cardiomyopathies - Surina,; Fontanella, Rosaria Anna; Scisciola, Lucia; Marfella, Raffaele; Paolisso, Giuseppe; Barbieri, Michelangela (Frontiers in Cardiovascular Medicine, 2021)
miR-21 is a 22-nucleotide long microRNA that matches target mRNAs in a complementary base pairing fashion and regulates gene expression by repressing or degrading target mRNAs. miR-21 is involved in various cardiomyopathies, including heart failure, dilated cardiomyopathy, myocardial infarction, and diabetic cardiomyopathy. Expression levels of miR-21 notably change in both heart and circulation and provide cardiac protection after heart injury. In the meantime, miR-21 also tightly links to cardiac dysfunctions such as cardiac hypertrophy and fibrosis. This review focuses on the miR-21 expression pattern and its functions in diseased-heart and further discusses the feasibility of miR-21 as a biomarker and therapeutic target in cardiomyopathies